OPTIMIZATION METHODS - Olimpia PECINGINA; Constantin BOGDAN; Dragos Vasile VÎGA (Fiabilitate şi Durabilitate)
Throughout the ages, man has continuously been involved with the process of optimization. In its earliest form, optimization consisted of unscientific rituals and prejudices like pouring libations and sacrificing animals to the gods, con- sulting the oracles, observing the positions of the stars, and watching the flight of birds. When the circumstances were appropriate, the timing was thought to be auspicious (or optimum) for planting the crops or embarking on a war.